The Relationship Between Nutritional Status And The Incidence Of Anemia In Pregnant Women At The Mayangan Jombang Community Health Center - Nikmatul Ulfa Nikmatul Ulfa; Siswati Siswati (International Journal of Health Engineering and Technology, 2026)
Anemia during pregnancy remains a major nutritional problem in Indonesia, leading to the risk of premature birth, postpartum hemorrhage, and maternal death. One contributing factor is malnutrition or Chronic Energy Deficiency (CED). This study aims to analyze the relationship between nutritional status and the incidence of anemia in pregnant women in the Mayangan Community Health Center, Jombang Regency. This analytical study, using a cross-sectional design, involved 183 pregnant women selected using a simple random sampling technique. Data were collected through measuring the Upper Arm Circumference (MUAC) and analyzing hemoglobin (Hb) levels. Data were analyzed using the Chi-Square test. The majority of respondents showed good nutritional status (73.8%) and did not experience anemia (55.7%). The results of the Chi-Square analysis showed a p-value of 0.028 (p < 0.05) with a χ² value of 5.222. There is a significant relationship between nutritional status and the incidence of anemia in pregnant women at the Mayangan Community Health Center. The better the mother's nutritional status, the lower the risk of anemia.